2015
DOI: 10.1589/jpts.27.2709
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bodyweight-based exercise with blood flow restriction on isokinetic knee muscular function and thigh circumference in college students

Abstract: [Purpose] The purpose of this study was to investigate the effects of bodyweight-based exercise with blood flow restriction on isokinetic muscular function and thigh circumference in college students. [Subjects and Methods] The subjects were 17 college students who were recruited and randomly assigned to bodyweight-based exercise with blood flow restriction and bodyweight-based exercise groups. Participants performed front lunges and squats at ratings of perceived exertion of 11–13 three times a week during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In the high-intensity movement patterns, quadriceps (knee extensors) and hamstring muscle groups (knee flexors) participate in the primary level movements (Xaverova et al, 2015). Quadriceps muscles, which are also responsible for walking, running, dynamic stabilization of the knee joint, postural balance, and body weight, play a primary role in extensional movement (Kang, Kim, Lee, & Kim, 2015). Knee flexors act as knee joint stabilizers during acceleration, divergence, deceleration and landing (Stolen, Chamari, Castagna, & Wisloff, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the high-intensity movement patterns, quadriceps (knee extensors) and hamstring muscle groups (knee flexors) participate in the primary level movements (Xaverova et al, 2015). Quadriceps muscles, which are also responsible for walking, running, dynamic stabilization of the knee joint, postural balance, and body weight, play a primary role in extensional movement (Kang, Kim, Lee, & Kim, 2015). Knee flexors act as knee joint stabilizers during acceleration, divergence, deceleration and landing (Stolen, Chamari, Castagna, & Wisloff, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that isotonic training with 15% of maximal voluntary isometric contraction (MVC) strength increased muscle size (14), but it is unknown what percentage of 1RM this corresponds to. Similarly, applying blood flow restriction during bodyweight exercises (i.e., lunges and squats) has demonstrated small (15) to no improvements (11) over exercise in the absence of blood flow restriction, but it is once again unknown what percentage of 1RM these bodyweight exercises correspond to or exactly what pressure was applied. Other low-intensity activities, such as walking (2) and cycling (1), have been shown to increase muscle size, illustrating that more studies are needed to examine the efficacy of blood flow restriction when combined with even lower loads (i.e., <20% 1RM).…”
Section: Introductionmentioning
confidence: 99%
“…The deficit range of the quadriceps strength serves as a criterion for an important clinical judgment; a deficit of less than 10% is considered the clinical milestone for returning an athlete back to sports 21 ) . Playing a major role in the quadriceps, the knee extensor muscle controls motion of the lower limbs and serves other important functions 22 , 23 ) such as supporting body weight and maintaining body alignment and stability. Assessment of muscular function provides useful rehabilitation measures for both general people and athletes, and applies readily and safely to restoration of muscle balance, recovery from muscle injury, and rehabilitation 14 , 24 , 25 , 26 ) .…”
Section: Discussionmentioning
confidence: 99%